Directive Speech Act Use In Conversation Frozen 1 Movie - Nova Hizkia Cristin; Ambelagin Ambelagin (Musamus Journal of Language and Literature, 2022)
This study identified the directive acts in the Frozen1 movie. In this study, the research design was a qualitative approach in which the researchers expressed the outcome in words and provided an explanation of the result. The researchers looked at a variety of directive speech acts. The data were analyzed by the theory from Kreidler (1998). There were some types of directive, command, request, order, and suggest. This research existed in the movie â€œFrozen 1â€. The researchers found 15 utterances that were uttered by the characters in the movie. The researchers found 5 utterances that expressed the commanding speech. Second, the researchers found 4 utterances that expressed the requesting speech. Third, the researchers found 4 utterances that expressed the suggesting speech and for the last, the researchers found 2 utterances. From the utterances that were found in the movie, the dominant type was commanding act.